Analisis Kinerja Jaringan 5G dalam Meningkatkan Konektivitas Internet of Things (IoT) - Fauzan Prasetyo Eka Putra; Dian Tri Agustina; Triana Selvia Khusnul Khotimah; Tarisha Ramadhanty (Pusat Riset dan Inovasi Nasional, 2025)
The 5G network represents a major technological advancement driving the progress of the Internet of Things (IoT), particularly through its ability to transmit data at high speeds with near-instant response times. It enables stable connectivity for a greater number of IoT devices within a single area without compromising network performance, thereby supporting the development of advanced applications such as smart cities, precision agriculture, smart grids, and modern healthcare services. In the energy sector, 5G enhances smart grid management by enabling more efficient energy distribution. In healthcare, it allows real-time monitoring of patients through IoT-based medical devices. Meanwhile, in the agricultural domain, 5G facilitates intelligent land management and supports more accurate decision-making. Overall, 5G strengthens IoT capabilities by providing highly precise and real-time data, which accelerates analytical processes and improves operational performance. Consequently, 5G plays a strategic role in advancing digital transformation across various industrial and social sectors, boosting productivity, operational efficiency, and service quality, while also opening new opportunities for future IoT implementations.